TEAMwork: Testing Emotional Attunement and Mutuality During Parent-Adolescent fMRI - Kerr, Kara L.; Cosgrove, Kelly T.; Ratliff, Erin L.; Burrows, Kaiping; Misaki, Masaya; Moore, Andrew J.; DeVille, Danielle C.; Silk, Jennifer S.; Tapert, Susan F.; Bodurka, Jerzy; Simmons, W. Kyle; Morris, Amanda Sheffield (Frontiers in Human Neuroscience, 2020)
The parent-child relationship and family context influence the development of emotion regulation (ER) brain circuitry and related skills in children and adolescents. Although both parents’ and children’s ER neurocircuitry simultaneously affect how they interact with one another, neuroimaging studies of parent-child relationships typically include only one member of the dyad in brain imaging procedures. The current study examined brain activation related to parenting and ER in parent-adolescent dyads during concurrent fMRI scanning with a novel task – the Testing Emotional Attunement and Mutuality (TEAM) task. The TEAM task includes feedback trials indicating the other dyad member made an error, resulting in a monetary loss for both participants. Results indicate that positive parenting practices as reported by the adolescent were positively correlated with parents’ hemodynamic activation of the ventromedial prefrontal cortex, a region related to empathy, during these error trials. Additionally, during feedback conditions both parents and adolescents exhibited fMRI activation in ER-related regions, including the dorsolateral prefrontal cortex, anterior insula, fusiform gyrus, thalamus, caudate, precuneus, and superior parietal lobule. Adolescents had higher left amygdala activation than parents during the feedback condition. These findings demonstrate the utility of dyadic fMRI scanning for investigating relational processes, particularly in the parent-child relationship.